Computer Aided Volume Measurement Using Osirix, A Free 3D-Rendering Software, In Preplanned Correction Of Enophthalmos With Diced Cartilage Graft - Kreshanti, Prasetyanugraheni; Bangun, Kristaninta (Jurnal Plastik Rekonstruksi, 2012)
Autologous costal diced cartilage graft is an option for replenishment of the volume deficit in residual enophthalmos following orbito-zygomatic trauma. However, in published journals referring this treatment option, quantitative volume measurement of the graft needed has not been established. Two patients with orbito-zygomatic fractures resulted from motorcycle accidents, presented with dystopia, entrapment of the eyeball, diplopia, and depressed malar eminence on the affected side. CT scans demonstrated orbital-floor disruption and herniation of the intra-orbital content into the maxillary sinus. Using OsiriX®, a free and open source medical imaging software, we calculated the volume discrepancy of the affected orbit. On coronal slices, the segmentation of the bony orbital region of interest of each single slice was performed and grouped to compute the volume. At surgery, diced cartilage grafts were inserted to the orbital cavity according to the calculated volume, to promote forwards shift of the eye globe position after releasing the entrapment and replacing the orbital floor. In both patients, good position of the eye globe was achieved. The aesthetic appearance was perceived as quite acceptable to the patients and other viewers. Transient diplopia settled within 3 months. We considered OsiriX® as a reliable tool for accurate quantitative measurement of diced cartilage graft volume in enophthalmos correction.